Information and Communication Technology on Course Leverage and the Development of Teacher Education at Kwara State College of Education, florin - Salau , K. K.; MUSTAPHA, A. m; ADEFILA, E.; IFABIYI, A. 0.; AJIBOLA, 0. E (International Journal of Educational Management, 2025)
The study was carried out to examine application of Information and Communicatio Technologies (ICTs) on course leverage and the development of teacher education i Kwara State College of Education, florin. Specifically, the study examined the influenc of ICTs on course leverage and development of teacher education. The study adopte descriptive survey and made use of questionnaire to elicit information from th respondents. Data gathered were analysed using inferential statistics oft-test. To ensur the instrument used for data collection is valid, it was given to experts in test an measure, while test and retest technique was employe to test the reliability. Th. i instrument was administered on respondents who were not part of the target population t w ce within an interval of two weeks. Data gathered from the two administrations wer subjected to Pearson product moment correlation and a coefficient obtained, 0. 86 wa considered high enough. This confirmed that the instrument was valid. The date analysed revealed that there was no significant difference between the mean ratings o, male and female lecturers on the influence of application of ICTs on course leverage. Furthermore, the result of the study showed that there was no significant difference between the mean ratings of male and female lecturers on the influence of application OJ ICTs on the development of teacher education. The study concluded that application oJ ICTs in tertiary institutions has the potentials of fostering development in the educational system. It also brought to light the synonymous opinions of male and female lecturers as regard the tendency of ICTs to serve as leverage in the development oj teacher education. On the basis of these findings, the study recommended that the State Government should provide adequate computers and other ICT resources and infrastructure to ensure a meaningful integration and implementation of ICT in teaching and learning process.